A study of takeoff motion in ski jumping using principal component analysis and computational fluid dynamics - Ikeda, S.; Shimada, T.; Bale, R.; Ueno, T.; Yamamoto, K.; Tsubokura, M. (10th International Congress on Science and Skiing, January 28 - February 1, 2025, Val di Fiemme, Italy, 2025)
INTRODUCTION: The motions of ski jumping are divided into four parts: in-run, takeoff, flight, and landing. The takeoff motion in which largely change jumpers` posture in a short time of about 0.2~0.3 seconds is considered to strongly affect the performance. However, suitable takeoff motions have not been biomechanically and aerodynamically identified. Therefore, in this study, we first constructed a simulation framework that can reproduce detailed posture changes during takeoff using markerless motion capture. Next, the various jumps are classified with principal component analysis. The purpose of this study is to clarify the relationship between postural change during takeoff and the unsteady aerodynamic forces using the constructed framework.